The Effect of Poultry Manure on Proximate Composition and in vitro Gas Production of Panicum maximum cv T 58 in the Derived Savanna Zone of Nigeria - Sodeinde, F.G.; Akinlade, J.A.; Aderinola, O.A.; Amao, S.R.; Alalade, J.A.; Adesokan, A.T. (Pakistan Journal of Nutrition, 2009)
The in vitro gas production and the proximate composition of field grown Panicum maximum cv T 58 (Guinea grass) harvested from poultry manured soil and harvested after 6 weeks of regrowth was determined. The experiment was a split plot design with three replicates. Poultry droppings increased the volume of the gas produced in both stem and leaf of P. maximum cv T 58. The result reveals that stems produce higher methane gas than the leaf. This indicates that the stem lost high energy compared to the leaves when fed to the ruminants. There were no significant differences (P > 0.05) in metabolizable energy (ME), organic matter digestibility (OMD) and short chain fatty acids (SFA) measured. Panicum maximum from fertilized poultry dropping recorded higher crude protein 8.40% content in the leaf compared with the stem of 5.08 %. Despite these variations, the forage generally contained adequate amounts of the minerals to meet livestock requirements. In production systems, the quality of Panicum maximum a major feed of grazing animals in south Western Nigeria could be enhanced by application of the poultry dropping to the soil.